Alzheimer’s Disease Dementia Guidelines for Diagnostic Testing: A Systematic Review (2013)
Alzheimer’s disease dementia (AD dementia) is one of the most common neurodegenerative diseases worldwide, with a growing incidence during the last decades. Clinical diagnosis of cognitive impairment and presence of AD biomarkers have become important issues for early and adequate treatment. We performed a systematic literature search and quality appraisal of AD dementia guidelines, published between 2005 and 2011, which contained diagnostic recommendations on AD dementia. We also analyzed diagnostic recommendations related to the use of brief cognitive tests, neuropsychological evaluation, and AD biomarkers. Of the 537 retrieved references, 15 met the selection criteria. We found that Appraisal of Guidelines Research and Evaluation (AGREE)-II domains such as applicability and editorial independence had the lowest scores. The wide variability on assessment of quality of evidence and strength of recommendations were the main concerns identified regarding diagnostic testing. Although the appropriate methodology for clinical practice guideline development is well known, the quality of diagnostic AD dementia guidelines can be significantly improved.